Factors associated with contraceptive ideation among urban men in Nigeria. (23rd May 2015) - Babalola, Stella; Kusemiju, Bola; Calhoun, Lisa; Corroon, Meghan; Ajao, Bolanle
Abstract: Objective: To determine factors influencing the readiness of urban Nigerian men to adopt contraceptive methods. Methods: The data were derived from a cross‐sectional household survey conducted in Ibadan and Kaduna between September and November 2012. The sample included 2358 men from both cities. An ideation framework was constructed and a multilevel analysis performed to identify factors associated with positive thinking about contraception. Results: Correlates of ideation operated at the individual, household, and community levels. There is considerable cluster‐level variability in ideation score. The key correlates included exposure to family planning promotion campaigns, education, age, religion, marital status, and community norms. Compared with no education, high education is associated with an approximately 6.7‐point increase in ideation score ( P < 0.001). Men with a high level of NURHI program exposure had an average ideation score that was about 3.4 points higher than for their peers with no exposure ( P < 0.001). The ideation score for Muslims was lower by approximately 1.7 points, on average, than for Christians ( P < 0.001). Conclusion: A comprehensive strategy of communication and behavior change activities surrounding contraceptive use should be tailored to meet the needs of specific groups of men. Community‐level interventions designed to mobilize community members and change social norms that hinder the spread of ideational characteristics that favor contraceptive use should be part of this comprehensive strategy.